A quality control study Plastic Container Packaging Corporation - Buan, Melanie C.; Maramba, Amyzola N.; Triunfante, Anna Marie R. (Diliman, Quezon City College of Engineering, 1999)
Plastic Container Packaging Corporation (PCPC) started its operation in 1967 as the pioneer in plastic manufacturing in the Philippines. Presently, the company uses conventional and ultraviolet (UV) machines. Curing time is greatly reduced in UV machines but printing defects are relatively higher compared to conventional machines. The group conducted a study on the UV machines using quality control techniques. It was found out that the bulk of printing defects in the UV machines fall under peel-off. Peel-off happens when the ink does not fully adhere to the bottle's surface. A crucial parameter in printing is the setting of the right air-gas combination for the Flame treatment of the bottles. This is crucial in preventing peel-off. The company has no set standards for the right air-gas combination for the flame treatment of the bottles. Oil seeps through the flamer from the compressor which also attributes to peel-off. The group recommends that a gas gauge be used. Further tests should be conducted to determine the right air-gas combination. The group also suggests that the company look into the possibility of using a non-lubricated cylinder to prevent oil contamination and thus reduce peel-off in the printing process.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Plastic Container Packaging Corporation .; Plastics industry and trade; Quality control